Indonesian or English? EFL Student Teachers’ Preference and Perception on the Language Use in the Classroom - Eddy Haryanto; Urip Sulistiyo; Miftahul Khairani; Retno Wulan (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT The purposes of this research were to investigate learners’ perception in teaching English using Bahasa and English, learners’ preference for language use as the medium of instruction, and the subjects that can be taught by using Bahasa. The participants were 57 EFL learners in the fourth semester at a university in Jambi Province, Indonesia. This research was designed in mix method by distributing a questionnaire and conducting a Focus Group Discussion (FGD) as the data collection techniques. The findings showed that the students were excited to have English as the medium of instruction in their classroom. However, they also welcome the L1 (Bahasa Indonesia). In addition, the learners preferred to have English as the medium of instruction in their English classroom. In view of this, the use of both their L1 and L2 should be balanced. Moreover, concerning the subjects taught, the learners need the use of English especially in the Listening and Speaking classrooms. ABSTRAK Penelitian in bertujuan untuk mengetahui persepsi mahasiswa mengenai pengajaran Bahasa Inggris dengan menggunakan Bahasa Indonesia dan Bahasa Inggris, pilihan mahasiswa dalam penggunaan bahasa tersebut sebagai media pengajaran di dalam kelas, dan jenis – jenis pelajaran yang bisa diajarkan dengan menggunakan Bahasa Indonesia. Peserta dalam penelitian ini adalah 57 mahasiswa semester empat pada salah satu universitas di Provinsi Jambi, Sumatra, Indonesia yang diambil melalui purposive sampling. Penelitian ini didesain dalam metode campuran melalui angket dan Diskusi Kelompok Terarah (FGD).  Hasil yang didapat menunjukkan bahwa siswa sangat senang menggunakan Bahasa Inggris dalam pengajaran di kelas. Namun, siswa juga tidak keberatan dengan penggunaan Bahasa Indonesia. Sebagai tambahan, siswa lebih memilih penggunaan Bahasa Inggris sebagai media pengajaran di dalam kelas. Oleh karena itu, penggunaan kedua Bahasa tersebut haruslah seimbang. Terkait dengan mata pelajaran, mahasiswa lebih memilih penggunaan Bahasa Inggris hanya dalam pengajaran “menyimak (listening)” dan “berbicara (speaking)” How to Cite: Haryanto, E. Sulistiyo, U. Wulan, R. (2016). Indonesian or English?  EFL Student Teachers’ Preference and Perception on the Language Use in the Classroom. IJEE (Indonesian Journal of English Education), 3(1), 46-59. doi:10.15408/ijee.v3i1.3941 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.3941